Functional analysis of a novel G87V TNFRSF1A mutation in patients with TNF receptor‐associated periodic syndrome. (4th September 2019) - Tsuji, S.; Matsuzaki, H.; Iseki, M.; Nagasu, A.; Hirano, H.; Ishihara, K.; Ueda, N.; Honda, Y.; Horiuchi, T.; Nishikomori, R.; Morita, Y.; Mukai, T.
Summary: Tumor necrosis factor (TNF) receptor‐associated periodic syndrome (TRAPS) is an autoinflammatory disease that is caused by heterozygous mutations in the TNFRSF1A gene. Although more than 150 TNFRSF1A mutations have been reported to be associated with TRAPS phenotypes only a few, such as p.Thr79Met (T79M) and cysteine mutations, have been functionally analyzed. We identified two TRAPS patients in one family harboring a novel p.Gly87Val (G87V) mutation in addition to a p.Thr90Ile (T90I) mutation in TNFRSF1A . In this study, we examined the functional features of this novel G87V mutation. In‐vitro analyses using mutant TNF receptor 1 (TNF‐R1)‐over‐expressing cells demonstrated that this mutation alters the expression and function of TNF‐R1 similar to that with the previously identified pathogenic T79M mutation. Specifically, cell surface expression of the mutant TNF‐R1 in transfected cells was inhibited with both G87V and T79M mutations, whereas the T90I mutation did not affect this. Moreover, peripheral blood mononuclear cells (PBMCs) from TRAPS patients harboring the G87V and T90I mutations showed increased mitochondrial reactive oxygen species (ROS). Furthermore, the effect of various Toll‐like receptor (TLR) ligands on inflammatory responses was explored, revealing that PBMCs from TRAPS patients are hyper‐responsive to TLR‐2 and TLR‐4 ligands and that interleukin (IL)‐8 and granulocyte–macrophage colony‐stimulating factor (GM‐CSF) are likely to be involved in the pathogenesis of TRAPS. These findings suggest that the newly identified G87V mutation is one of the causative mutations of TRAPS. Our findings based on unique TRAPS‐associated mutations provide novel insight for clearer understanding of inflammatory responses, which would be basic findings of developing a new therapeutic and prophylactic approach to TRAPS. Abstract : We found a novel G87V mutation in TNFRSF1A gene in two patients with TNF receptor‐associated periodic syndrome (TRAPS) in a family. Functional analyses of the G87V mutation have revealed that cell surface expression of the mutant TNF‐R1 was decreased, which is similar to that with the previously identified pathogenic T79M mutation. The peripheral blood mononuclear cells from TRAPS patients harboring the G87V mutation showed increased mitochondrial reactive oxygen species and enhanced production of IL‐8 and GM‐CSF in responses to TLR ligands.